The Influence Of Organizational Culture, Work Environment, And Leadership On The Performance Of Restaurant Employees In Batam Mediated By Motivation - Muhammad Donal Mon; Yuswardi Yuswardi; Alvin Henk Saputra Tan (Cita Konsultindo Research Center, 2023)
The article aims to analyze the relationship connection the Independent variables, namely Organizational Culture, Work Environment, and Leadership, and the Dependent variable, namely Employee Performance, which is mediated by Motivation. The data collection technique used was primary by distributing questionnaires to respondents. This study collected data from 280 respondents distributed to restaurant employees in Batam, Indonesia. To test these variables using the Partial Least Squares (PLS) and Structural Equation Modeling (SEM) methods. The research results are that Organizational Culture got positive significant towards employee performance. Work environment got positive significant towards employee performance. Leadership got positive significant towards employee performance. Motivation got positive significant towards employee performance. Organizational culture got positive significant towards motivation. Work environment got positive significant towards motivation. The leadership got positive significant towards motivation. Organizational culture got positive significant towards employee performance which are mediated by motivation. Work got positive significant towards employee performance variables which are mediated by motivation. Work environment got positive significant towards employee performance variables which are mediated by motivation. This proves that motivation can mediate those variables.